Antiarrhythmic Effect of SGLT-2 Inhibitors in high-degree AV Block Caused by Heart Failure: A Case Report - Ngurah Agung Reza Satria Nugraha Putra; I Ketut Susila (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. The antiarrhythmic effect of SGLT-2 inhibitors, particularly empagliflozin, is a very interesting topic to discuss further. 2. In patients with high degree AV block due to HF in rural areas, the use of SGLT-2 inhibitors is quite rare in Indonesia. - Background: According to WHO's Top 10 Global Health Threats, non-communicable diseases such as heart failure contribute to more than 70% of all deaths worldwide. Several studies have shown that SGLT-2 inhibitors can considerably reduce HF. As research progresses, SGLT-2 inhibitors may lessen the risk of arrhythmias in HF patients. Case Summary: A 57-year-old female with uncontrolled hypertension came to the ED after collapsing at home. The vital signs and physical examination are normal. The preliminary ECG showed a high degree AV Block with multiple multifocal PVC. Early laboratory revealed mild hypokalemia. The patient experienced a seizure the next day, and an ECG showed total AV block with a non-sustained VT episode with PVC R on T. Following critical cardiac care and stabilization, the patient underwent echocardiography, which showed mild MR and AR with a reduced ejection fraction (47.7%). Once the patient's condition has stabilized, the patient is given 1x10mg Empagliflozin PO. Discussion: SGLT-2 inhibitors are beneficial in the treatment of heart failure and arrhythmia. SGLT-2 inhibitors have antiarrhythmic effects through a variety of pathways, such as lowering preload and afterload, inhibition of sodium-hydrogen exchange in myocardial cells, and suppression of the sympathetic nervous system.